2018
DOI: 10.1093/ecco-jcc/jjy175
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Single-centre Outcomes After Proctocolectomy With Ileoanal Anastomosis for Paediatric Ulcerative Colitis

Abstract: Background and Aims: Childhood-onset ulcerative colitis [UC] requires total colectomy in onequarter of patients at some point of their disease. The study objective was to evaluate long-term outcomes after proctocolectomy with ileoanal anastomosis [IAA] for paediatric UC. Methods: Medical records of all children undergoing proctocolectomy with IAA for UC during 1985-2016 in Helsinki University Hospital were retrospectively assessed. Data on disease history, diagnostic and operative details, occurrence of surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Although the majority of patients who developed pouchitis did so within the first year as found in previous studies (17), the first episode could occur after 2 or 3 years. Although this is higher than previous reports among adults with a pouchitis rate of 23% to 46% (10), and closer to a recent report of a pouchitis rate of 70% (29), importantly, we also found that 71% of patients had good or excellent pouch function at 1 year with a median of 5 (IQR 4-6) bowel movements daily, consistent with existing pediatric data (7,12,30,31).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the majority of patients who developed pouchitis did so within the first year as found in previous studies (17), the first episode could occur after 2 or 3 years. Although this is higher than previous reports among adults with a pouchitis rate of 23% to 46% (10), and closer to a recent report of a pouchitis rate of 70% (29), importantly, we also found that 71% of patients had good or excellent pouch function at 1 year with a median of 5 (IQR 4-6) bowel movements daily, consistent with existing pediatric data (7,12,30,31).…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in the higher range of previously reported pouchitis rates in children with IBD, 31-73% [11][12][13] depending on definition and time of follow-up. We also found that 71% of patients had good or excellent pouch function at 1 year with a median of 5 (IQR 4-6) bowel movements daily, consistent with existing pediatric data 11,14,28,29 .…”
Section: Discussionsupporting
confidence: 88%
“…90% of patients in another study would recommend IPAA surgery to others (97). Pouch abandonment and conversion to permanent ileostomy following IPAA undertaken in childhood is reported to occur in 9% and 13% of patients in two series, albeit with a relatively short median follow-up of 7 and 4 years, respectively (98,99).…”
Section: Complications and Outcomesmentioning
confidence: 93%
“…This figure exceeds the SBO risk reported after appendectomy (from 1 to 10%) 1,2, 7 or after open cholecystectomy (6.4%) 1 is similar than 10 to 25% reported in general intestinal surgery, 8 but less than 29% reported with proctocolectomy with ileoanal anastomosis. 9 Fredriksson et al 10 Only SB affected 0.6 (0.1-3.9) 0.60 1.4 (0.1-13) 0.80 0.9 (0.2-3.8) 0.96…”
Section: Discussionmentioning
confidence: 99%
“…This figure exceeds the SBO risk reported after appendectomy (from 1 to 10%) 1,2,7 or after open cholecystectomy (6.4%) 1 is similar than 10 to 25% reported in general intestinal surgery, 8 but less than 29% reported with proctocolectomy with ileoanal anastomosis. 9 Fredriksson et al After an acute phase of NEC, conservatively managed patients may develop intestinal strictures mostly in the colon, 11 whereas in surgical patients intestinal anastomotic strictures may develop. 12 In a reoperation for SBO after acute onset of NEC or SIP, it may be impossible to determine whether the actual cause of obstruction was adhesions, anastomotic stricture, or both.…”
Section: Discussionmentioning
confidence: 99%